(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Dengue virus infection is increasing in frequency as well as its complications. Profound/prolonged dengue shock syndrome causes metabolic acidosis leading to different metabolic and electrolyte abnormalities. Endocrine glands may be involved by shock, bleeding, and inflammation and may present with transient abnormalities in hormone levels. This unusual expanded dengue syndrome may require close follow up for proper management. Besides, diabetes mellitus and obesity are risk factors for severe dengue and mortality. This review article summarizes the endocrine and metabolic aspects of dengue infection in brief. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2): 66-70